Metabolite Profiling and Anti-Inflammatory Potential of East Kolaka Forest Honey: Targeting Protein Denaturation through GC-MS/MS Characterization - Hariana, Hariana; Wahyuni, Wahyuni; Irnawati, Irnawati; Fitrawan, La Ode Muhammad; Munasari, Dian; Yodha, Agung Wibawa Mahatva; Purnama, La Ode Muhammad Julian; Fristiohady, Adryan (Program Studi Farmasi Universitas Mandala Waluya, 2025)
Forest honey is a natural product produced by wild bees that gather nectar from various types of flowers, creating a unique chemical composition influenced by the biodiversity of the surrounding environment. This honey contains bioactive compounds such as phenolics, flavonoids, terpenoids, and volatile substances that contribute to its pharmacological properties, particularly as an anti-inflammatory agent. This study aimed to identify bioactive compounds in forest honey from East Kolaka using Gas Chromatography-Mass Spectrometry (GC-MS) and to evaluate its anti-inflammatory activity through in vitro assays, including red blood cell (RBC) membrane stabilization, protein denaturation inhibition, and nitric oxide (NO) production inhibition. GC-MS analysis revealed several volatile compounds with antioxidant, antimicrobial, and anti-inflammatory properties. The RBC membrane stabilization assay showed increased membrane stability as honey concentration increased, reaching 92.55% at 100 mg/L compared to 97.00% for sodium diclofenac. In the protein denaturation assay, East Kolaka forest honey had an IC?? value of 12.70?±?0.02?mg/L, categorized as moderate, while the NO inhibition assay recorded an IC?? of 2.97?±?1.34?mg/L, indicating strong activity, approaching that of vitamin C (1.07?±?0.39?mg/L). Statistical tests showed significant differences (p < 0.05) in all tested parameters compared to positive controls. These results support the potential of East Kolaka forest honey as a natural anti-inflammatory agent through mechanisms involving membrane stabilization, protein protection, and nitric oxide suppression.